IMPROVING THE MANAGEMENT QUALITY OF ATHLETIC MANAGEMENT RUNNING NUMBERS, LUMPS AND THEMS IN SMP NEGERI 3 INGIN JAYA ACEH BESAR DISTRICT - Azhari (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
This study aims to improve the quality of the management model of athletic sports club training management, especially running, jumping and throwing numbers at SMP Negeri 3 Wish Jaya, Aceh Besar district, and specifically aims to assess the extent of analyzing the capabilities of the athletic sports club management model in SMP Negeri 3. Want Jaya, Aceh Besar District, in this research study was carried out at SMP Negeri 3 Wish Jaya, Aceh Besar District. The method used is a qualitative analysis research method, which only assesses, looking at the feasibility of the development of management of the athletic sports club management. The results of the research obtained show that: 1) improve capabilities, facilitate the management / management of athletic sports, especially running, jumping and throwing numbers at SMP Negeri 3 Want Jaya, Aceh Besar District, 2) make an evaluation plan for the management of athletic sports club training management, especially numbers running, jumping and throwing at SMP Negeri 3 Wish Jaya, Aceh Besar District, 3) making monthly, weekly, and daily training programs, 4) applying rules to be more disciplined, focused and motivated in practicing, 5) being able to organize properly about scheduling, determination of a training location, especially the athletic sports club at SMP Negeri 3 Wish Jaya, Aceh Besar District. The results of the research and its discussion show that the management process and results of the management of Aceh Athletic sports in the area are still low, this is because the management, management, recruitment and financing processes are still lacking / are still in the stages of improvement towards a more advanced direction - average up to 75%.